A Moodle virtual learning classroom as a teaching strategy for high school students in the subject of Physics - LOPEZ MACHUCA, OSWALDO MARCEL; REGALADO LEON, MARGARITA; Santamaria López, Teresa; Martínez Isaac, Roger (Revista Minerva, 2024)
This study focused on the use of the Moodle tool and its usefulness and effectiveness in the teaching-learning process. The objective was to analyze how the Moodle platform performs as a teaching strategy for third-year high school students at the Juan Henríquez Coello school in the city of Machala. For this, a methodology with a quantitative experimental approach was used. To collect the data, an evaluation survey was applied through six activities related to physics. The survey was applied before and after implementing the Moodle tool, and a sample of 81 third-year high school students was selected. For data processing, the JAMOVI statistical program was used, which allowed a comparative analysis of the findings. The results obtained from the different activities before and after the implementation of Moodle reveal a clear pattern of improvement in average grades when Moodle is used as a tool for activity management. Therefore, it was concluded that this tool not only improves the academic performance of students, but also contributes to creating a more consistent, collaborative and enriching learning environment. Keywords: Moodle platform, teaching strategy, physics teaching, high school.